Laparoscopic Management of Huge Ovarian Cysts - A. Alobaid; A. Memon; S. Alobaid; L. Aldakhil (Hindawi Limited, 2013)
Objectives. Huge ovarian cysts are conventionally managed by laparotomy. We present 5 cases with huge ovarian cysts managed by laparoscopic endoscopic surgery without any complications. Materials and Methods. We describe five patients who had their surgeries conducted in a tertiary care center in Riyadh, Saudi Arabia (King Fahad Medical City). Results. Patients age ranged between 19 and 69 years. Tumor markers were normal for all patients. The maximum diameter of all cysts ranged between 18 and 42 cm as measured by ultrasound. The cysts were unilocular; in some patients, there were fine septations. All patients had open-entry laparoscopy. After evaluation of the cyst capsule, the cysts were drained under laparoscopic guidance, 1-12 liters were drained from the cysts (mean 5.2 L), and then laparoscopic oophorectomy was done. The final histopathology reports confirmed benign serous cystadenoma in four patients and one patient had a benign mucinous cystadenoma. There was minimal blood loss during surgeries and with no complications for all patients. Conclusion. There is still no consensus for the size limitation of ovarian cysts decided to be a contraindication for laparoscopic management. With advancing techniques, proper patients selection, and availability of experts in gynecologic endoscopy, it is possible to remove giant cyst by laparoscopy.